Anti-Inflammatory and Prebiotic Potential of Ethanol Extracts and Mucilage Polysaccharides from Korean Yams (Dioscorea polystachya and Dioscorea bulbifera) - So-Yoon Park; Van-Long Truong; Su-Gyeong Jeon; So-Young Choe; Razanamanana H. G. Rarison; Byoung-Hoon Yoon; Ji-Won Park; Hye-Jeong Jeong; Woo-Sik Jeong (Foods)
Korean yams are abundant in bioactive compounds with significant health-promoting properties. This study evaluated the anti-inflammatory potential of ethanol and water extracts from Dioscorea polystachya and Dioscorea bulbifera in RAW 264.7 macrophage cells. Among the extracts, the 95% ethanol extract exhibited the most potent inhibition of reactive oxygen species (ROS) and nitric oxide (NO) production, warranting further exploration of its mechanisms of action. Further analysis revealed that the ethanol extract modulated key inflammatory signaling pathways, including MAPK and NF-κB, contributing to its anti-inflammatory activity. Additionally, mucilage polysaccharides, a key bioactive component of Korean yams, were extracted and characterized for their structural and functional properties. These polysaccharides demonstrated immune-enhancing effects by reducing ROS and NO production while increasing phagocytic activity in the RAW 264.7 cells. Their prebiotic potential was also assessed through microbial growth assays, which showed an enhanced proliferation of beneficial bacteria such as Lactobacillus and Bifidobacterium. Furthermore, the adhesion assays using Caco-2 intestinal epithelial cells revealed that these polysaccharides promoted probiotic adhesion while inhibiting the adhesion of pathogenic bacteria. These findings highlight the bioactive potential of ethanol extracts and mucilage polysaccharides from Korean yams, emphasizing their promising applications as anti-inflammatory, immune-modulating, and prebiotic agents for functional food and nutraceutical development.